2020
DOI: 10.1016/j.celrep.2020.108526
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Surfaces of the Cdc15 F-BAR Domain Create a Membrane Platform That Coordinates Cytoskeletal and Signaling Components for Cytokinesis

Abstract: Highlights d Cdc15 F-BAR domain uses opposite faces to bind membrane and proteins simultaneously d F-BAR non-membrane-binding faces create extensive surfaces for binding partners d Cdc15 F-BAR organizes both structural and signaling components for cytokinesis d F-BAR domains can dictate nanoscale spacing and function of actin-based structures Authors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 69 publications
2
32
0
Order By: Relevance
“…We found that Pxl1 phosphorylation reduces its ability to bind the F-BAR domain of Cdc15 in vitro, and because Pxl1-Cdc15 F-BAR domain interaction is the major mechanism of Pxl1 CR recruitment (Snider et al, 2020), our results provide a mechanistic explanation for the phosphorylation-mediated change we observe in Pxl1 localization in vivo. It also seems possible however that phosphorylation regulates Pxl1 protein levels given that we observed a ~two-fold increase in the abundance of Pxl1(9A) using tags for Pxl1 detection.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…We found that Pxl1 phosphorylation reduces its ability to bind the F-BAR domain of Cdc15 in vitro, and because Pxl1-Cdc15 F-BAR domain interaction is the major mechanism of Pxl1 CR recruitment (Snider et al, 2020), our results provide a mechanistic explanation for the phosphorylation-mediated change we observe in Pxl1 localization in vivo. It also seems possible however that phosphorylation regulates Pxl1 protein levels given that we observed a ~two-fold increase in the abundance of Pxl1(9A) using tags for Pxl1 detection.…”
Section: Discussionsupporting
confidence: 56%
“…The N-terminus of Pxl1 is the site of Cdk1 phosphorylation and contains CR targeting information (Pinar et al, 2008). Pxl1 interacts directly with the F-BAR protein Cdc15 (Roberts-Galbraith et al, 2009;Bhattacharjee et al, 2020;Snider et al, 2020).…”
Section: Cdk1-mediated Phosphorylation Inhibits Pxl1 Binding To Cdc15's N-terminus But Not Its C-terminusmentioning
confidence: 99%
See 3 more Smart Citations